GESTÃO UNIVERSITÁRIA EM TEMPOS DE PANDEMIA: CARACTERÍSTICAS E CONTRIBUIÇÕES DA IMPROVISAÇÃO ESTRATÉGICA - Lessa, Ester Onofre Barbosa (2022)
The management of public universities is challenging for several reasons, in particular, specificities such as organizational complexity and professional bureaucracy make any change a lengthy process. The materialization of actions, in this context, requires from the organizational agents the ability to adapt plans and creativity to search for alternative solutions, respecting the institutional rules. In this context, improvisation has been presented as a contributory solution, especially in the face of unexpected events that demand urgent responses. This research examined how manifestations of improvisation helped in the responses given by a Brazilian public university to the demands related to the Covid-19 pandemic. The study is based on concepts related to public management, strategic management and improvisation. This is qualitative research, whose data were collected through interviews and documents. Data were analyzed using document analysis and narrative analysis techniques. Results showed the manifestation and contribution of improvisations, especially in situations that demanded immediate solutions, under pressure, to make the established plans viable. We found the presence of individual and collective improvisation. In individual improvisations, the experience of the organizational agents was a highlight. Collective improvisations, in turn, were more frequent in the case of more comprehensive solutions, covering different areas and stakeholders. The demand for quick responses stimulated creativity to reconcile speed of response and compliance with institutional norms, showing greater dynamics in interactions between individuals, areas and groups, especially when compared to a non-pandemic context. We concluded that improvisation has been a practice in university management activities, although not openly recognized. In this sense, the relevance of the agents experience and learning was highlighted when finding solutions, through improvisation, without harming any legal aspect of the processes involved.